2022
DOI: 10.3390/dermatopathology9020015
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Cutaneous Squamous Cell Carcinomas Following Treatment for Graft-versus-Host Disease: A Case Report and Review of Risk Factors

Abstract: A 19-year-old female with a history of pre-B cell acute lymphocytic leukemia (ALL) presented with two aggressive cutaneous squamous cell carcinomas (C-SCC) in the right hand. The patient was diagnosed with pre-B cell ALL at four years of age. She underwent chemotherapy with initial remission. However, recurrence of the pre-B cell ALL required an unrelated allogeneic cord hematopoietic stem cell transplant (alloHSCT). Post-transplant, the patient developed Graft-Versus-Host Disease (GVHD), which was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Among studies that exclusively included pediatric HSCT recipients, the total number of participants was 6209, with 18 developing skin cancers 8,23–25 . In addition, three case studies reported a total of six pediatric HSCT recipients who developed skin cancers, resulting in a total of 67 pediatric HSCT recipients who went on to develop a form of skin cancer 26–28 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among studies that exclusively included pediatric HSCT recipients, the total number of participants was 6209, with 18 developing skin cancers 8,23–25 . In addition, three case studies reported a total of six pediatric HSCT recipients who developed skin cancers, resulting in a total of 67 pediatric HSCT recipients who went on to develop a form of skin cancer 26–28 …”
Section: Resultsmentioning
confidence: 99%
“…There were a total of 32 SCCs, followed by 25 BCCs, 3 melanomas, 3 Kaposi sarcomas affecting the skin, 1 Merkel cell carcinoma, and 1 myxofibrosarcoma. Of the six cases where body sites were reported, skin cancers were observed at the following sites: Kaposi sarcoma (abdomen, face, and upper and lower limbs) with positive immunohistochemical staining for human herpesvirus‐8 26 ; SCC in situ on the left cheek 28 ; nodular‐type and superficial‐type SCC in the nasolabial fold 28 ; SCC in situ on the left temple and hand lesions 28 ; two aggressive SCCs on the dorsum of the right hand 27 ; and one SCC on the left leg 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, tacrolimus (Fig. 1), is recommended for the treatment of autoimmune diseases, rheumatoid arthritis, and lichen planus [5], as well as in bronchial asthma treatments, dermatological disorders as vitiligo, psoriasis, atopic dermatitis [6], eye diseases like uveitis [7], and retinoblastomas [8].…”
Section: Introductionmentioning
confidence: 99%